2020
DOI: 10.1084/jem.20202057
|View full text |Cite
|
Sign up to set email alerts
|

The BAFFling persistence of memory B cells

Abstract: Although BAFF/BLyS and its receptor, BAFFR, play critical roles in naive B cell survival, the pathways involved in the persistence of memory B cells are largely unknown. In this issue of JEM, two groups, Müller-Winkler et al. (https://doi.org/10.1084/jem.20191393) and Lau et al. (https://doi.org/10.1084/jem.20191167), take complementary approaches to identify an essential role for BAFFR in the survival of memory B cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Studies have shown that RelB deficiency in humans results in impairment of B cell development, with an absence of CD27+ MBCs leading to severe B cell immunodeficiency and shortage in the secretion of antibodies ( 169 ). Overall, BAFF is required for GC-independent MBC generation, and MBC survival depends on the synergy of BCR- and BAFF-mediated activation of the NFκB pathway ( 170 ).…”
Section: The Nfκb Signaling System In Memory B Cellsmentioning
confidence: 99%
“…Studies have shown that RelB deficiency in humans results in impairment of B cell development, with an absence of CD27+ MBCs leading to severe B cell immunodeficiency and shortage in the secretion of antibodies ( 169 ). Overall, BAFF is required for GC-independent MBC generation, and MBC survival depends on the synergy of BCR- and BAFF-mediated activation of the NFκB pathway ( 170 ).…”
Section: The Nfκb Signaling System In Memory B Cellsmentioning
confidence: 99%
“…Antibodies targeting B cell surface molecules CD20 and CD19 can successfully deplete B cells but do not protect against IgA nephropathy 8 . Because BAFF is considered to drive B cell function and development, 9 this molecule is a potential target of new therapies for autoimmune disease. Several strategies have been developed to block BAFF and APRIL in vivo and have been successful in clinical trials including for SLE 10 …”
mentioning
confidence: 99%